Hearing the call of mitochondria: Insight into its role in sensorineural hearing loss - Haojia He; Zhuoxue Han; Shuai Cheng; You Zhou (Neurobiology of Disease)
Sensorineural hearing loss (SNHL) is a prevalent and complex auditory disorder with a multifactorial pathogenesis, in which mitochondrial dysfunction plays a pivotal role. Mitochondria are abundantly localized in critical structures of the inner ear, where they not only provide the substantial energy required for auditory transduction but also regulate key cellular processes. Growing evidence suggests that mitochondrial impairment, characterized by excessive reactive oxygen species (ROS) generation, dysregulated inflammatory responses, disrupted apoptosis, and mitochondrial DNA (mtDNA) mutations, is closely linked to the onset and progression of SNHL. Recent advances in mitochondria-targeted therapeutic strategies, such as antioxidant delivery, promotion of mitochondrial biogenesis, and mitochondrial gene therapy, have shown promising preclinical results. However, significant challenges remain in translating these approaches into clinical practice, particularly in terms of targeted delivery, long-term efficacy, and potential side effects. This comprehensive review systematically examines the molecular mechanisms underlying mitochondrial involvement in SNHL pathogenesis, evaluates recent progress in mitochondria-targeted interventions, and discusses current limitations and future directions in this rapidly evolving field. By integrating current knowledge and identifying key research gaps, this review aims to provide a solid theoretical foundation and fresh perspectives for the development of effective therapeutic strategies for SNHL.